Photoinduced decomposition of acetaldehyde on a reduced TiO2(110) surface: involvement of lattice oxygen. Issue 45 (2nd November 2016) - Xu, Chenbiao; Yang, Wenshao; Guo, Qing; Dai, Dongxu; Yang, Xueming
Abstract : A simple model reveals that BBO atoms are involved in the photo-induced decomposition of CH3 CHO on TiO2 (110). Abstract : We have investigated the photo-induced decomposition of acetaldehyde (CH3 CHO) on TiO2 (110) at 400 nm using temperature programmed desorption (TPD) and time of flight (TOF) methods. Formate (HCOO − ) and acetate (CH3 COO − ) products have been detected. The initial step in the decomposition of CH3 CHO on TiO2 (110) is the formation of a CH3 CHO bidentate intermediate in which the carbonyl O atom of CH3 CHO is bound to the five-fold-coordinated Ti 4+ lattice site (Ti5c ) and the carbonyl C atom is bound to a nearby bridge-bonded oxygen (BBO) atom. During 400 nm irradiation, the decomposition of the CH3 CHO bidentate mainly occurs through two parallel pathways. Part of the CH3 CHO bidentate on the surface undergoes a facile photoreaction to form formate by ejecting the methyl radical of CH3 CHO into gas phase. The remaining CH3 CHO bidentate reacts on the surface to produce acetate by transferring the H atom of –CHO to a BBO site or by ejecting the H atom into the vacuum. Thus we have found that BBO atoms are intimately involved in the photo-induced decomposition of CH3 CHO on TiO2 (110).